120k views
4 votes
Which equation could be used to find the length of the hypotenuse?

Which equation could be used to find the length of the hypotenuse?-example-1
User Randyaa
by
4.7k points

2 Answers

2 votes

ay duud yo answer is A.

User DLKJ
by
4.8k points
5 votes

Option A:
$6^(2)+11^(2)=c^(2)$ is the length of the hypotenuse

Step-by-step explanation:

From the figure, we can see that the given triangle is a right angled triangle.

Hence, we can determine the length of the hypotenuse using Pythagoras theorem.

Thus, we have,


$a^(2)+b^(2)=c^(2)$

where a and b are the lengths of the sides of the triangle. And c is the hypotenuse.

Thus, substituting the lengths of the sides
a=6 ,
b=11 and
c=c is the hypotenuse.

Substituting these values in the equation, we get,


$6^(2)+11^(2)=c^(2)$

Thus, the length of the hypotenuse is
$6^(2)+11^(2)=c^(2)$

User Pankaj Cheema
by
4.6k points